Revisiting Intention Among Tourist: The Role of Facilitating Infrastructure and Service Quality - Rahmat Ingkadijaya; Meinita Dewi Sulistian; Adhi Trirachmadi Mumin (Islamic University of Kalimantan MAB Banjarmasin, 2022)
The study aims to investigate the effect of facilities and service quality on return visit intentions. This research uses Smart PLS path analysis. Tourists that visited Kampoeng Wisata Cinangneng Recreation Park, Ciampea District, Bogor Regency, were studied. This study had 147 participants. The results showed: (1) Direct Effects showed that the facility had no significant effect on satisfaction and revisit intention, while service quality did, then satisfaction did; (2) Indirect Effects showed that the facility has no significant effect on the intention to revisit through satisfaction, while service quality does; In this study, service quality from addressing complaints and difficulties, speed and readiness to deliver services, providing a safe and comfortable area, and understanding tourists' needs can boost customer satisfaction and return intentions. The manager of Kampoeng Wisata Cinangneng Recreation Park should maintain and improve service quality to keep tourists coming back.